Connections: A Teaching & Learning Newsletter Vol. 1, Issue 2 - Vajoczki, Sue; Deane, Patrick; Marquis, Beth; Head, Milena; Colangelo, Marc; Burgstahler, Sheryl; Paddon, Natalie; Fenton, Nancy; Fleisig, Robert; Josan, Pannu (Centre for Leadership in Learning, 2010)
Biannual newsletter of the Centre for Leadership in Learning, including: Director's Welcome; From the President; Thinking About Teaching and Learning; Learning Spaces; Signature Pedagogies; Teaching Tips; TA Notes; SoTL News; CLL Profile; Field Notes; Teaching with Technology; Award-Winning Instruction.
Keywords: Seven principles for good practice in undergraduate education; Inquiry-based learning; Universal Design; Accessibility; Scholarship of Teaching and Learning (SoTL); Computer-aided grading; Teaching with technology; Teaching awards